CULTIVATION OF VEGETABLES AND FISH USING THE AQUAPONICS SISTEM (DFT MODEL) IN CV TMR - Wawan Gunawan; Sofiyan Firdaus; Bambang Ali (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2021)
Communities and companies in Indonesia are experiencing economic difficulties due to the corona pandemic (Covid-19). The purpose of this service is to help people or companies affected by Covid-19 that apply environmentally friendly technology, are easy to apply and generate benefits for partners, especially employees who have been laid off so they can work again, while the applied technology used is aquaponic techniques for cultivating vegetables and fish which mutually beneficial, the method of collaboration used is a partnership with one of the companies affected by the impact of Covid-19 (CV TMR), the use of unused goods or materials that are in the partner also to optimize dead land to be used and utilized into productive areas. The aquaponics model used is the DFT (Deep Flow Technique) system, DFT is a hydroponic planting system that uses puddles in the installation and uses slow-flow circulation. This system uses electricity as a pump drive so that it can easily circulate nutrients to all plant roots, the process of making until harvesting fish is 3 months with the results of partners getting an additional stage of 1,632,000, while the benefits obtained from partners are the environmental area becomes more comfortable and comfortable to be an attraction for visitors. for the next program an aquaponics system will be built on a land of 30 mx 1.5 m with the assumption of ten times the profit per harvest (per three months).